Improvements to Visual Design on the Online News Portal ABC.com by Employing Usability and Eye Tracking Methods - Rahmat Budi Soedirdjo; Argo Hadi Kusumo; Markus Hartono (Engineering Proceedings)
This study aims to enhance the visual design of ABC.com, a leading Indonesian online news portal, by using usability and eye-tracking methods. As news media transitions from print to digital, maintaining an optimal user experience is crucial. This study addresses design deficiencies on ABC.com, particularly related to news accessibility, search functionality, and the impact of advertisements. This research employs questionnaires and eye-tracking technology to identify user behavior and validate the findings. Key usability aspects, such as content accessibility, error prevention, and visual appeal, are analyzed to improve the website’s layout. The eye-tracking results reveal that users focus mainly on the center of the screen, often missing critical elements like the latest news and the search engine. This study proposes enhancements in typography, contrast, and page layout, based on the identified needs. The final design of ABC.com improved by enhancing efficiency, clarity, aesthetics, readability, and user comfort. The redesign showed mean improvements of 0.16, 0.41, 0.65, 0.32, and 0.54 in these criteria, respectively, indicating a notable enhancement in usability. This study’s findings offer a practical guideline that can be directly applied to enhance similar online news platforms in Indonesia.